A comparison of 2020 health policy responses to the COVID-19 pandemic in Canada, Ireland, the United Kingdom and the United States of America. Issue 5 (May 2022) - Unruh, Lynn; Allin, Sara; Marchildon, Greg; Burke, Sara; Barry, Sarah; Siersbaek, Rikke; Thomas, Steve; Rajan, Selina; Koval, Andriy; Alexander, Mathew; Merkur, Sherry; Webb, Erin; et al.
Highlights: We compare COVID-19 health policy responses in Canada, Ireland, UK and US. All countries faced common challenges including procuring PPE and scaling-up testing capacity. Challenges were magnified due to pre-existing health workforce shortages and insufficient infrastructure. Health system capacity and governance and political leadership all shaped country responses. Innovative solutions were employed to change care delivery and increase surge capacity. Abstract: This paper compares health policy responses to COVID-19 in Canada, Ireland, the United Kingdom and United States of America (US) from January to November 2020, with the aim of facilitating cross-country learning. Evidence is taken from the COVID-19 Health System Response Monitor, a joint initiative of the European Observatory on Health Systems and Policies, the WHO Regional Office for Europe, and the European Commission, which has documented country responses to COVID-19 using a structured template completed by country experts. We show all countries faced common challenges during the pandemic, including difficulties in scaling-up testing capacity, implementing timely and appropriate containment measures amid much uncertainty and overcoming shortages of health and social care workers, personal protective equipment and other medical technologies. Country responses to address these issues were similar in many ways, but dissimilar in others, reflecting differences in health system organization and financing, political leadership and governance structures. In the US, lack of universal health coverage have created barriers to accessing care, while political pushback against scientific leadership has likely undermined the crisis response. Our findings highlight the importance of consistent messaging and alignment between health experts and political leadership to increase the level of compliance with public health measures, alongside the need to invest in health infrastructure and training and retaining an adequate domestic health workforce. Building on innovations in care delivery seen during the pandemic, including increased use of digital technology, can also help inform development of more resilient health systems longer-term.